(untitled) (International relations and international law Journal, 2024)
The presented research article provides an in-depth analysis of the multidimensional impact of climate change on international trade and the global economic system. The study focuses on a comprehensive examination of the direct and indirect effects of climatic factors, such as extreme weather events, which lead to significant disruptions in supply chains, production processes and infrastructure. The paper emphasises the critical link between environmental change and international economic activity, justifying how climate change can cause fluctuations in global markets through agricultural losses and infrastructure damage. The article proposes a methodological approach aimed at generating strategies for adapting to and minimising the negative impacts of climate change that are suitable for implementation at national and international levels. The strategies developed by the authors include proposals to improve environmental sustainability and economic efficiency, contributing to sustainable development and stability in a changing climate. This approach involves the active inclusion of international co-operative initiatives as well as the development of new technologies and innovations to adapt international trade to new environmental realities. This research article will be useful for academic researchers, policy analysts and practitioners in the field of international trade and economics, providing a theoretical and practical framework for developing climate change adaptation strategies. Key words: climate, trade, economics, sustainability, strategies.